Effects of Early Intervention on Visual Function in Preterm Infants: A Randomized Controlled Trial - Fontana, Camilla; De Carli, Agnese; Ricci, Daniela; Dessimone, Francesca; Passera, Sofia; Pesenti, Nicola; Bonzini, Matteo; Bassi, Laura; Squarcina, Letizia; Cinnante, Claudia; Mosca, Fabio; Fumagalli, Monica (Frontiers in Pediatrics, 2020)
Objectives: To determine the effectiveness of an early intervention program in enhancing visual function in very preterm infants. Methods: We conducted a RCT. We included preterm infants born between 25+0 and 29+6 weeks of gestational age (GA), without severe morbidities, and their families. Infants were randomized to either receive Standard Care (SC) or Early Intervention (EI). SC, according to NICU protocols, included Kangaroo Mother Care and minimal handling. EI included, in addition to routine care, parental training according to the PremieStart program, and multisensory stimulation (infant massage and visual interaction) performed by parents. Visual function was assessed at term equivalent age (TEA) using a prevalidated battery evaluating ocular spontaneous motility, ability to fix and follow a target, reaction to color, stipes discrimination and visual attention at distance. Results: Seventy preterm (EI n=34, SC n=36) infants were enrolled. Thirteen were excluded according to protocol. Fifty-seven infants (EI=27, SC=30) were assessed at TEA. The two groups were comparable for parental and infant characteristics. In total, 59% of infants in the EI group achieved the highest score in all the nine assessed items compared to 17% in the SC group (p=0.001): all infants in both groups showed complete maturation in four items, but EI infants showed more mature findings in the other five items (ocular motility both spontaneous and with target, tracking arc, stripes discrimination and attention at distance). Conclusions: Our results suggest that EI has a positive effect on visual function maturation in preterm infants at TEA. Trial Registration: clinicalTrial.gov (NCT02983513)